Duplicated Renal System with H Shaped Ureter: An Extraordinary Anomaly. (28th January 2016) - Akbulut, Fatih; Savun, Metin; Ucpinar, Burak; Sahan, Murat; Arslan, Burak; Ozgor, Faruk; Simsek, Abdulmuttalip; Berberoglu, Ahmet Yalcın; Baykal, Murat; Binbay, Murat
Abstract : Duplex collecting systems are the most commonly encountered anomaly of the urinary system. Complete duplex system with an H shaped ureter is a very rare situation. There are only two reported H ureter cases in the literature. Herein, we aimed to present an H shaped ureter case, which was identified while performing ureterorenoscopy to a 48-year-old female patient due to a right distal ureteral stone.